Phrenic Nerve Injury With Ice Slush In Open Heart Surgery- Myth Vs Reality - Sazzad, Md Faizus (Indian Association of Cardiovascular-Thoracic Surgeons (IACTS), 2021)
63rd Annual Congress of Indian Association of Cardiovascular-Thoracic Surgeons (IACTS)